ANALISIS KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN RAJA AMPAT TAHUN 2010 – 2014 - Isir, Trivosa; Ilat, Ventje; Mawikere, Lidia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Local generated revenue is one indicators a successfully on local financials independence in financing governments activiy, because of it regency of King Ampat tried to explore financial resources by local tax and local charges exist to maximize general income. The study aims to determine the extent of the contribution of local taxes and local charges to the local generrated income. The methods used in this research is qualitative diskriptif by explaining the contribusions and the average contribution of each component of local tax and local charge as well as the total contributions of local tax and local charge periode 2010-2014 are presented in table as well as its descriptions. Results from this study indicate that the contribution of local tax and local charge to the local generated income in the regency of King Ampat during the periode of 2010-2014 are fluctuated. The biggest contributios of local tax is occurred in 2014 and the lowest contribution occurred in 2013. While the contribution of the largest in the levies was occurred in 2010 and the lowest contribution occurred in in the year 2013. Keywords :Analysis Contribution, Local Tax, Local Retribution, Local Revenue